2021
DOI: 10.3390/nano11092393
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Antifungal Activity of Graphene Oxide and Fungicides against Fusarium Head Blight In Vitro and In Vivo

Abstract: Plant pathogens constantly develop resistance to antimicrobial agents, and this poses great challenges to plant protection. Therefore, there is a pressing need to search for new antimicrobials. The combined use of antimicrobial agents with different antifungal mechanisms has been recognized as a promising approach to manage plant diseases. Graphene oxide (GO) is a newly emerging and highly promising antimicrobial agent against various plant pathogens in agricultural science. In this study, the inhibitory activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 43 publications
1
26
0
Order By: Relevance
“…For example, fungicide-resistant strains emerge after long-term use [ 27 ]. Graphene application has provided a new tool for controlling plant pathogens [ 19 ]. Recent findings have demonstrated that graphene’s antimicrobial activities are greatly influenced by its physical and chemical properties, such as functional groups [ 52 ], concentration [ 53 ] and morphology [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, fungicide-resistant strains emerge after long-term use [ 27 ]. Graphene application has provided a new tool for controlling plant pathogens [ 19 ]. Recent findings have demonstrated that graphene’s antimicrobial activities are greatly influenced by its physical and chemical properties, such as functional groups [ 52 ], concentration [ 53 ] and morphology [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that the inhibitory effect of graphene was concentration-dependent; at low concentrations (50, 100 mg/L), its inhibitory effect is limited, while at high concentrations (200, 500 mg/L), its inhibitory effect is significant. Previous studies have suggested that graphene can not only inhibit the growth of many pathogens by itself but also has a synergistic effect with fungicides [ 12 , 14 , 19 ]. It has been demonstrated that GO can significantly hinder the growth of mycelium and the germination of a variety of fungal pathogen spores afflicting plants, including Fusarium graminearum , Fusarium poaea , and Fusarium oxysporum [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, GO was prepared with the Hummer’s method [ 27 ]. Physical loading of Pyr onto the surface of GO was conducted to obtain the GO–Pyr nanocomposite [ 28 ]. For screening the optimal combination ratio between GO and Pyr, the inhibitory effects of GO–Pyr combined at different ratios (1:9, 2:8, 3:7, 6:4, 5:5, 4:6, 7:3, 8:2 and 9:1) on the mycelial growth of FG was tested.…”
Section: Methodsmentioning
confidence: 99%
“…GO combined with mancozeb, cyproconazol, and difenoconazole fungicides exhibited synergistic inhibitory effects on the mycelial growth and biomass as well as spore germination of F. graminearum compared to single fungicides, and also in a field experiment pronouncedly reduced Fusarium head blight disease incidence and disease severity in wheat plants. Upon GO-fungicide treatment, mycelia were shrunk and deformed, and membrane fusion, due to the changes in cell membrane permeability and loss of cell wall integrity, along with disappearance of cytoplasm, was observed [ 201 ]. The IC 50 value related to the inhibition of mycelium growth of Magnaporthe oryzae by carbendazim−GO nanocomposite was 0.28 μg/mL, compared to 0.64 μg/mL estimated at single carbendazim application, suggesting 2.29-fold higher antifungal activity.…”
Section: Applications Against Plant Patogenic Microorganismsmentioning
confidence: 99%